Dengue social representations related to newspaper publications in the northeast of Argentina - Agustín Villarreal; Lucía Genzone; Maria José Villarreal; Rosa Yanina Macchi; Natalia Soledad Amerio (Gaceta Médica Espirituana)
Background: Dengue is an infectious disease, is transmitted by the Aedes aegypti mosquito, especially in tropical regions. In the last few years, the city of Posadas (Misiones-Argentina) faces an increase in the number of cases that has led the provincial government to decree a sanitary and epidemiological emergency in 2020.